(untitled) (Marketing Journal, 2025)
This article presents an in -depth analysis of the distinctive features of the development of Uzbekistanʼs industrial sector. The study covers the structural composition of the industry, territorial specialization, innovation processes, and № 1 48 digitalization. It examines the impact of economic potential, technology transfer, investment environment, and workforce training on sector development. Existing challenges and possible solutions are analyzed. The topic is vital for enhancing the sustainab ility and competitiveness of the national economy by improving industrial policy. The research findings offer practical recommendations on industrial modernization, cluster and cooperation development, and the implementation of new technologies.